Investigation of the frequency of IgG antibodies to T. gondii in consumers of raw meatballs - Acik, Y; Felek, S; Bulut, V; Ayar, A (Royal Soc Medicine Press Ltd, 2005)
[Abstract Not Available]
Keywords: Human Toxoplasmosis; Seroprevalence